Structural investigations of poly(ethylene terephthalate)- graft-polystyrene copolymer films - Nasef, Mohamed Mahmoud (Wiley Periodicals, Inc., 2002)
Structural investigations of poly(ethylene terephthalate)-graft-polystyrene (PET-g-PS) films prepared by radiation-induced grafting of styrene onto commercial poly- (ethylene terephthalate) (PET) films were carried out by FTIR, X-ray diffraction (XRD), and differential scanning calorimetry (DSC). The variation in the degree of crystallinity and the thermal characteristics of PETfilms was correlated withthe amount of polystyrene grafted therein (i.e., the degree of grafting). The heat of melting was found to be a function of PET crystalline fraction in the grafted films. The grafting is found to take place by incorporation of amorphous polystyrene grafts in the entire noncrystalline (amorphous) region of the PET films and at the surface of the crystallites. This results in a decrease in the degree of crystallinity with the increase in the degree of grafting, attributed to the dilution of PET crystalline structure with the amorphous polystyrene, without almost any disruption in the inherent crystallinity.